Metformin and Vascular Diseases: A Focused Review on Smooth Muscle Cell Function - Mingying Deng; Dan Su; Suowen Xu; Peter J. Little; Peter J. Little; Xiaojun Feng; Liqin Tang; Aizong Shen (Frontiers Media S.A., 2020)
Metformin has been used in diabetes for more than 60 years and has excellent safety in the therapy of human type 2 diabetes (T2D). There is growing evidence that the beneficial health effects of metformin are beyond its ability to improve glucose metabolism. Metformin not only reduces the incidence of cardiovascular diseases (CVD) in T2D patients, but also reduces the burden of atherosclerosis (AS) in pre-diabetes patients. Vascular smooth muscle cells (VSMCs) function is an important factor in determining the characteristics of the entire arterial vessel. Its excessive proliferation contributes to the etiology of several types of CVD, including AS, restenosis, and pulmonary hypertension. Current studies show that metformin has a beneficial effect on VSMCs function. Therefore, this review provides a timely overview of the role and molecular mechanisms by which metformin acts through VSMCs to protect CVD.